(untitled) (Scientific journal of the Fergana State University, 2024)
This article contains information about some of the units found in people’s speeches, the appreciation of the language, and some insights into agnonims. To this day, the author has interrupted some cases of little attention. The study provides examples of the use of agnonim words. Commentary dictionaries, artifacts, and the language of live speech have served as sources for examples.